L’imposition d’un syntagme : la Société de l’Information - Bernard MIÈGE (Tic & Société)
The term (or syntagm) Information Society has a long history, already forty years, marked by the failure of several attempts to conceptualize. He holds within it a range of stakes, first social-discursive reactivated last dozen years with transnational development programs of information and communication technologies (ICTs) and at the World Summits on the Information Society (Geneva in 2003 and Tunis in 2005); and then, proper communication stakes that the paper attempted to update: the informationalisation; the promotion of technologies and networks more than contents; the modification and the expansion of media systems and the control of transnational flows of information and communication. Finally the use of the phrase is far from harmless.